2017
DOI: 10.17583/ijep.2017.2584
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination, self-esteem, academic performance, and well-being: A moderated mediation model

Abstract: The current study attempts to examine integrated effects of procrastination, selfesteem, and academic performance on well-being in a sample of Turkish undergraduate students (N = 348). Results confirm prior evidence suggesting that procrastination and self-esteem were important predictors of well-being. Results also indicated that both procrastination and academic performance have direct and interactive effects on self-esteem. Self-esteem mediated the relationships between procrastination and well-being. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 54 publications
5
51
0
3
Order By: Relevance
“…Findings of this current study are in line with the findings of the previous studies, which reported that students who believe that they were helpless tend to develop academic procrastination behavior (Duru & Balkis, 2017;Johnson & Bloom, 1995;Park & Sperling, 2012). Among this type of procrastinators, academic tasks are perceived to be overwhelmingly uncontrollable and threatening, up to the point where they believe paying adequate effort to finish them on time is pointless (Carden, Bryant, & Moss, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Findings of this current study are in line with the findings of the previous studies, which reported that students who believe that they were helpless tend to develop academic procrastination behavior (Duru & Balkis, 2017;Johnson & Bloom, 1995;Park & Sperling, 2012). Among this type of procrastinators, academic tasks are perceived to be overwhelmingly uncontrollable and threatening, up to the point where they believe paying adequate effort to finish them on time is pointless (Carden, Bryant, & Moss, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Studies over decades indicated that academic procrastination can be triggerred internally (by the procrastinators themselves) or externally (by the social environment of the procrstinators). Variables such as laziness, stress and motivation (He, 2017), as well as self- (Klassen, Krawchuk, & Rajani, 2008;Rakes & Dunn, 2010), self-esteem (Duru & Balkis, 2017), self-determined motivation (Rakes & Dunn, 2010), and self-efficacy (Klassen et al, 2008;Steel, 2010) have been reported to be the internal factors of procrastination. Factors such as negative evaluation from others (Saddler & Buley, 1999), and peer influence (Chen, Shi, & Wang, 2016) are the examples of external factors of academic procrastination.…”
Section: Factors Of Academic Procrastinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Dahası bireylerin akademik ertelemeleri arttıkça görevleri yerine getirmede isteksizlik ve sorumluluktan kaçma söz konusu olabileceği için, arkadaş ve öğretmenleri ile de ilişkilerinden sorunlar yaşayabilecek, akademik başarıları düşebilecek dolayısıyla okuldan daha az doyum elde edebileceklerdir. Araştırmanın akademik ertelemenin okul doyumunu negatif yönde yordadığına ilişkin bu bulgusu, alan yazındaki araştırmalar ile de desteklenmektedir (Balkıs, 2013;Chow, 2011;Duru ve Balkıs, 2017).…”
Section: Sonuç Ve Tartışmaunclassified